Flow-injection amperometry at microfabricated silicon-based μ-liquid–liquid interface arrays - Scanlon, M.; Berduque, A.; Strutwolf, J.; Arrigan, Damien (Pergamon-Elsevier Science Ltd, 2010)
Geometrically regular silicon membrane-based micropore arrays were employed for defined arrays of micrometer-sized interfaces between two immiscible electrolyte solutions (μITIES). These were incorporated into a poly(tetrafluoroethylene) (PTFE) hydrodynamic cell. Electrochemistry at the μITIES array was undertaken following gellification of the organic phase using polyvinyl chloride (PVC) and flowing an aqueous phase over the array surface. Cyclic voltammetric characterization of asymmetric diffusion profiles on either side of the μITIES was accomplished under flowing conditions using positively and negatively charged (TEA+ and 4-OBSA−, respectively) model analyte species. Incorporation of an ionophore (dibenzo-18-crown-6 ether) into the organogel allowed the ion-transfer detection of two oligopeptides (phenylalanine dipeptide and lysine dipeptide) within the available potential window under stationary and flowing conditions.Flow rate studies with TEA+ indicated that the amperometric peak currents do not obey the Levich equation, due to diffusion dominating the mass transport, as opposed to convection. The influence of the applied potential () on the amperometric response of the oligopeptides was studied and hydrodynamic voltammograms (HDVs) for the individual oligopeptides were subsequently constructed. The data presented provide a basis for the use of silicon membrane-based μITIES arrays in flow analytical methods.